Perceived work situation and work ability among persons who are working one year after stroke - Ingrid Lindgren; Hélène Pessah-Rasmussen; Gunvor Gard; Christina Brogårdh (Medical Journals Sweden, 2022)
Objective: To explore how persons who have returned to work perceive their work situation and work ability one year after stroke. Design: Cross-sectional design. Subjects: A total of 88 persons of working age (mean age 52 (standard deviation; SD 8) years, 36% women), with mild to moderate disabilities following stroke, who had returned to work within one year after stroke participated in the study. Methods: A survey including a questionnaire regarding psychological and social factors at work (QPS Nordic) and 4 questions from the Work Ability Index (WAI) was posted to the participants. Results: According to the QPS Nordic survey, 69-94% of respondents perceived their work duties as well defined, and were content with their work performance. Most participants had good social support at work and at home. Between 51% and 64% of respondents reported that they seldom felt stressed at work, seldom had to work overtime, or that work demands seldom interfered with family life. According to the WAI ≥75% of respondents perceived their work ability as sufficient, and they were rather sure that they would still be working 2 years ahead. Conclusion: Persons who have returned to work within one year after stroke appear to be content with their work situation and work ability. Appreciation at work, well-defined and meaningful work duties and support seem to be important for a sustainable work situation